Evaluación económica y social de cuatro municipios liderados por alcaldesas en el departamento del Chocó (2018)
After 28 years of regional elections in Colombia, the women of the Department of Chocó, between 2012 and 2016 won seven mayoralties. The population of Chocó are made up of ethnic minorities -black and indigenous- victimized by state violence and machismo; which motivated the research questions: What has been the scope of the governments of the woman in the reduction of the violence of gender and of State? What have they been done to reduce the feminization of poverty and machismo in these territories? The research methodology is deductive, taken through direct surveys of leaders of social and communal organizations and direct verification of the information provided. The study concludes that it is difficult to achieve great cultural changes in the political and in the family in four years or less of government; and above all, when it is urgent to think of new forms of popular election, to reduce corruption and Government Plans become more important.